Transformations of aesthetic and health values associated with the body and their impact of social behavior (Field study at King Faisal University) - Alsalem, Nourah Abdullah; Mohammed, Ahlam Alataa (Journal of Humanities & Social Sciences, 2025)
This study was Aimed at Identify the Transformations of Body's of Beauty and Health and Their Impact on Social behaviour. It used the Sample-Style Social Survey Curriculum and the Identification Tool. It was Applied to a Sample of Students at King Faisal University in College of Applied Medical Arts and Sciences. The Sample was 321 Female Students. It Produced Several Results, Including: One of the Behavioural Indicators of Changing Aesthetic Values Related to Standards of Attention to Appearance and Dress is the Student's Compatibility with The Modern Image of Female Beauty by Global and Local Culture in order to obtain Social Acceptance and using Fragrance as an important criterion in Attention to Appearance to keep up with the latest fashion trends, The Results Showed that One of the behavioural Manifestations of Transformation of Healthy Values Related to Exercise and Dieting is the use of Modern Techniques to Know The Ways in Which Sports and Diets are Developed. The use of Supplements and Vitamins to Mimic Beautiful Girls and Celebrities.The results further showed that value guidance on beauty and health values and its relationship to the student's body image satisfaction behaviour constrained the body image with specific models; This has affected her behaviour in the event of satisfaction or dissatisfaction with her body image, and cultural pressures about ideal standards of beauty and health are reasons for dissatisfaction with her body image; This led to unhealthy behaviors to control their desires.
Keywords: Aesthetic; Health; King Faisal University; Social behaviour; The Body; Transformations; Values